HUBUNGAN KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN DENGAN KEPUASAN KERJA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH NGANJUK - Andryas Tristina Hendrawati (Universitas Islam Kadiri, 2019)
The purpose of this research is 1) To know the correlation of Individual Characteristic with Nursing Work Satisfaction at Inpatient Room of RSUD Nganjuk, and 2) To know the relation of Job Characteristic with Nursing Work Satisfaction at Inpatient Room of RSUD Nganjuk. Respondents in this study were Inpatient Nurses in addition to VIP and VVIP which amounted to 40 people. Data collection was done by distributing questionnaires using Likert scale 1-5, where the assessment criteria depends on positive questions. The value of the 1 reviewer disagrees, the value 2 states less agree, the value 3 states agree, and the value 4 states strongly agree. Data analysis technique used is descriptive analysis which is intended to get a discription of respondents, also to know the description of each existing research variables are Individual Characteristics and Job Characteristics as an independent variable and Job Satisfaction as a dependent variable. The way to interpret existing data, is by going through the frequency tab and analyzing it according to the number and frequency. The result of the research proves that there is positive correlation between individual characteristic and nurse work satisfaction at inpatient room of RSUD Nganjuk. This can be shown with the cumulative mean of 4.09 which is in the range of very satisfied, There is a positive relationship between job characteristics with job satisfaction of nurse work satisfaction at inpatient room of RSUD Nganjuk. This can be shown by the cumulative mean of 4.08 which is in a very satisfied range.